Score-Valued Decision Making Models Based on Inverse Soft Matrices - Seda Erdinç; Emin Aygün (Sahand Communications in Mathematical Analysis)
In this work, we introduce some useful concepts in soft set theory, such as $\overline{α}$-inverse intersection and $\overline{α}$-inverse union of inverse soft sets, together with the type soft $\overline{α}$-upper, $\overline{α}$-lower, $\overline{α}$-intersection and $\overline{α}$-union of inverse soft matrices. Our main contribution is of proposing a new decision-making method associated with inverse soft sets and inverse soft matrices.